2002
DOI: 10.1248/jhs.48.570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grape Seed Polyphenols on Serum and Hepatic Lipid Contents and Fecal Steroid Excretion in Normal and Hypercholesterolemic Rats.

Abstract: The effects of grape seed polyphenol (GSP) administered orally at doses of 0.01-1.0 g/kg per day to normal and hypercholesterolemic rats for 28 and 36 days, respectively, was evaluated by measuring changes both in the concentrations of serum and hepatic lipids and in fecal steroid excretion. Body weight gain decreased dose-dependently both in normal and hypercholesterolemic rats. Relative weight of the liver was significantly lower in normal rats given more than 0.2 g/kg GSP compared with control rats. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
(37 reference statements)
1
17
1
Order By: Relevance
“…Studies that compared rats given a powdered diet (7) or a GSPE solution (22) did not find an increase in body weight compared with those given a standard diet. However, excessive GSPE may cause a reduction in body weight and reduce food intake (22). In the present results, 3 mg of GSPE added to a standard diet did not increase body weight.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies that compared rats given a powdered diet (7) or a GSPE solution (22) did not find an increase in body weight compared with those given a standard diet. However, excessive GSPE may cause a reduction in body weight and reduce food intake (22). In the present results, 3 mg of GSPE added to a standard diet did not increase body weight.…”
Section: Discussioncontrasting
confidence: 56%
“…According to the manufacturer's data sheet, GSE used in the present study contains polyphenols. It was reported that polyphenols can decrease TG concentration in the blood of rats and guinea pigs by changing lipid metabolism in the liver (Aprikian et al, 2003;Zern et al, 2003;Nakamura and Tonogai, 2002). Therefore, the decreased TG concentrations observed in the present study might not be a toxicological change but rather an effect due to polyphenols in GSE.…”
Section: Discussionmentioning
confidence: 45%
“…Studies that compared rats given a powdered diet (7) or a GSPE solution (22) did not find an increase in body weight compared with those given a standard diet. However, excessive GSPE may cause a reduction in body weight and reduce food intake (22). In the present results, 3 mg of GSPE added to a standard diet did not increase body weight.…”
Section: Discussionmentioning
confidence: 97%